2019
DOI: 10.4103/2045-9912.266985
|View full text |Cite
|
Sign up to set email alerts
|

“Real world survey” of hydrogen-controlled cancer: a follow-up report of 82 advanced cancer patients

Abstract: Advanced cancer treatment is a huge challenge and new ideas and strategies are required. Hydrogen exerts antioxidant and anti-inflammatory effects that may be exploited to control cancer, the occurrence and progression of which is closely related to peroxidation and inflammation. We conducted a prospective follow-up study of 82 patients with stage III and IV cancer treated with hydrogen inhalation using the "real world evidence" method. After 3-46 months of follow-up, 12 patients died in stage IV. After 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 37 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…We have conducted a voluntary field survey in patients diagnosed with cancer who inhaled hydrogen at home or at rehabilitation centers from 2014 to 2019. 2 Follow-up was performed on 82 patients with advanced (stage III and IV) cancer. The patients used the Hydrogen-oxygen Atomizer (AMS-H-03, Shanghai Asclepius Meditec Co., Ltd., Shanghai, China), which provided 66.7% hydrogen with mixed 33.3% oxygen with gas flow at 3000 mL/min.…”
Section: R Eal W Orld S Urvey Of H Ydrogen O Ncologmentioning
confidence: 99%
See 2 more Smart Citations
“…We have conducted a voluntary field survey in patients diagnosed with cancer who inhaled hydrogen at home or at rehabilitation centers from 2014 to 2019. 2 Follow-up was performed on 82 patients with advanced (stage III and IV) cancer. The patients used the Hydrogen-oxygen Atomizer (AMS-H-03, Shanghai Asclepius Meditec Co., Ltd., Shanghai, China), which provided 66.7% hydrogen with mixed 33.3% oxygen with gas flow at 3000 mL/min.…”
Section: R Eal W Orld S Urvey Of H Ydrogen O Ncologmentioning
confidence: 99%
“…Subsequently, it was discovered that the patient's improvements and recovery were due to the large amount of hydrogen gas contained in the holy water. Since a real world survey of 82 patients with advanced cancer from China was reported, 2 “hydrogen oncology” obtained the real world evidence for the first time. The articles used in this oncology review were retrieved by replicating the search terms of Chen et al 2 An electronic search of the Medline database for literature describing clinical hydrogen therapy for cancer patients from 2000 to 2019.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the support of hydrogen inhaler AMS-H-01/AMS-H-03 provided by Asclepius Meditec Co., Ltd., tens of animal studies or pilot clinical trials based on inhaled gas which combines H 2 (concentration of ~66%) with O 2 (concentration of ~34%) were accomplished and published. 14 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 Additionally, recent formal clinic trials based on the same inhaler AMS-H-01/AMS-H-03 also revealed positive results in respiratory diseases, such as allergic rhinitis, asthma, chronic obstructive pulmonary disease, etc. Especially, it is recommended to use the mixed gas of 66.6% H 2 /33.3% O 2 for treating coronavirus disease-19 (COVID-19) patients as described in the Diagnosis and Treatment Protocol for Novel Coronavirus Pneumonia, 7 Edition released by National Health Commission of China, 55 and such guideline is also republished in English by the World Health Organization China Office.…”
Section: Introduction Of H Ydrogen B Iomedicinementioning
confidence: 99%
“…56 Moreover, a survey report regarding 82 cancer patients with the help of the same inhaler AMS-H-01 also demonstrated that in patients with advanced cancer, inhaling gas with H 2 concentration of 64–67% can improve patients’ quality of life and control cancer progression. 53 Therefore, how to provide safe and durable hydrogen-oxygen inhalers with higher H 2 concentration is key factor to expedite and realize the hydrogen biomedicine. Search strategy is shown in .…”
Section: Introduction Of H Ydrogen B Iomedicinementioning
confidence: 99%